Tim Colter: The Edge of Violence - Book 2 Book 2 - Johnstone, William W.; Johnstone, J. A. (New York, New York : Kensington Books, 2017)
"It is the fall of 1867. Twenty-two years have passed since Tim Colter and his family were ambushed on the Oregon Trail, forcing the young boy to grow up, forge ahead, and find an unlikely ally in one-eyed mountain man Jed Reno. Now a widowed deputy U.S. marshal and Civil War veteran, Colter is finally ready to remarry and settle down--until a dangerous new assignment [involving the building of the Union Pacific Railroad] becomes a life-or- death struggle for the soul of a town and the heart of its people"--Dust jacket flap.
Keywords: Union Pacific Railroad Company -- Fiction; Widowers -- Fiction; Marshals -- Fiction; Railroads -- Fiction; United States -- History -- Civil War, 1861-1865; Veterans; Fiction